Uji Aktivitas Antibakteri Ekstrak Etanol Dan Dekokta Daun Jambu Kristal (Psidium guajava L. Cultivar Kristal) Terhadap Bakteri Bacillus cereus dan Staphylococcus aureus - Izzati, Sheila Nur; Munawaroh, Rima (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2026)
Background: Diarrhea is often caused by bacterial infections, including Bacillus cereus and Staphylococcus aureus. The irrational use of antibiotics can lead to antimicrobial resistance, highlighting the need for alternative therapies derived from natural products. Crystal guava leaves (Psidium guajava L. cultivar Kristal) are known to contain bioactive compounds with potential antibacterial properties; however, the effectiveness of their ethanolic extract and decoction has not been widely reported. Objective: This study aimed to evaluate and compare the antibacterial activity of ethanolic extract and decoction of crystal guava leaves against Bacillus cereus and Staphylococcus aureus, as well as to identify the major classes of compounds responsible for the observed activity. Methods: Extraction was carried out using maceration with 96% ethanol and decoction with water. Antibacterial activity was assessed using the well diffusion method at concentrations of 5%, 10%, 20%, and 40%. Identification of active compounds was performed through Thin Layer Chromatography (TLC) and TLC-bioautography analyses. Results: Both the ethanolic extract and the decoction exhibited antibacterial activity that increased with rising concentrations. The highest inhibition zones were observed at a concentration of 40%. The ethanolic extract demonstrated stronger antibacterial activity than the decoction, with the highest effectiveness against S. aureus. Bioautography analysis revealed that flavonoid compounds, strongly suspected to be quercetin derivatives, were the primary contributors to the antibacterial activity. Conclusion: Crystal guava leaf extract, particularly the ethanolic extract, shows significant antibacterial activity against B. cereus and S. aureus, with flavonoids identified as the key active compounds. These findings support the potential of crystal guava leaves as a natural source of antibacterial agents.